Generative AI Implementation in Enterprises: Lessons From a Case Study of Enhanced IT Service Management - Biswas, Baidyanath (Wiley, 2026)
The recent rise of Generative Artificial Intelligence (GenAI) is fundamentally changing the way businesses operate, with many now investing heavily in this Technology. However, businesses are still exploring ways to extract value from GenAI and develop organisational capabilities. In this practitioner paper, we describe how Apollo Tyres Limited (ATL), a traditional tyre manufacturer in India, utilised GenAI to transform its IT service desk operations and the tangible results it achieved from this integration. We identify the following four capabilities that ATL developed using GenAI: (i) enhanced management of customer interactions, such as overcoming delays due to multi-lingual conversations; (ii) proactive resolution of incidents, such as faster categorisation based on their textual descriptions; (iii) proactive management of IT assets, such as dynamic prediction of potential failures and system inefficiencies; and (iv) strategic analysis of operational data, such as a GenAI-driven frequently asked questions system. In addition, we illustrate ATL's actions to facilitate GenAI implementation in two broad categories: (i) building a foundation for GenAI implementation and (ii) realising GenAI-enabled capabilities. Seven lessons learnt are consequently generated to guide other companies in similar efforts to implement GenAI.
PUBLISHED
Keywords: Generative Artificial Intelligence; Sociotechnical Systems; Practitioner Paper; Value Realisation; Qualitative Study; Digital Engagement; Digital Humanities; Digital Technologies